Hepatitis C virus infection - Poma, Pedro A. (2011)
Hepatitis C virus is transmitted by direct contract with blood of an infected person. Most patients do not present symptoms during the acute or chronic phases. After two or three decades some patients progress to compensated cirrhosis, still asymptomatic. Antibodies in a blood test often come as a surprise because there is no association with the episode of contagion. Pregnancy brings the possibility of adverse effects to the mother or child. Current therapy does offer certainty of cure, depending on the viral genotype, and provokes adverse effects that might be severe. Decompensated cirrhosis causes most of the deaths associated with this infection; few patients develop hepatocellular carcinoma. Viral reproduction causes viral particles different from the original, characteristic that has prevented the development of vaccines. Current prevention consists in avoiding contact with infected blood. This article reviews infection with hepatitis C virus including the most recent progress in treatment. There is need to educate the general public about the effects of this virus on public health.